Factors Related to Health Resilience in Students Affected by Disaster at Campus Graha Ananda Palu - Sadli Syam; Muhammad Sabri Syahrir; Muhammad Aji Satria; Iin Irawati (Journal of Public Health and Pharmacy, 2025)
Introduction: Palu City, located in Central Sulawesi Province, is one of the most vulnerable areas disaster, intervention countermeasures disaster that has been This focus on intervention recovery source power and development infrastructure. while on intervention poor mental health get attention. Follow stages disaster in Palu City, when these are the people affected disaster in Palu City now currently in phase recovery going to resilience, namely restore normal condition and strengthen Power stand public to disaster. Research This aiming for inspect relationship preparedness, mental health and behavior health post disaster to resilience health of affected students disaster at the Institute Health Technology and Business Graha Ananda, Palu City, to be able to strengthen resilience health and able adapt to threat, danger, serious disturbance from disaster. Methods: Study This conducted at the Institute Technology and Health Business Ananda Building, Palu City, with use design observational cross sectional. Sample study This that is students of the Institute of Health Technology and Business Graha Ananda Palu City which was affected disaster as many as 55 people. Data is collected use questionnaire that has been validity and reliability tests were conducted along with with sheet observation. Data analysis was carried out with univariate and bivariate with using fisher exact test and likelihood as an alternative to the chi-square test. Results: Research results show that behavior health post disaster influential significant to resilience health, things This indicated p- value of 0.004, which means the better behavior health individual after disaster, increasingly big his contribution to ability for recover and survive (resilience health). Preparedness post disasters also have significant relationship with resilience health, with p value of 0.026, this show that individual or a more society Ready face situation post-disaster tend own resilience better health good. On the other hand, post-traumatic mental health disaster No own significant relationship with resilience health, because p -value of 0.112, which means that the condition post mental health disaster in context This No in a way direct influence level resilience health. Conclusion: Individual with level preparedness and implementing behavior good health after experience disaster tend show resilience better health Good However No existence significant relationship between post mental health disaster with resilience health indicates that resilience health Possible influenced by other factors such as support social from family, friends, and community can become factor important in resilience, individuals who feel supported in a way emotional or own access to network strong social tend more easy recover from trauma or stress caused by disaster.